2018
DOI: 10.1002/fuce.201800083
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Ionomer Binder with Shorter Side‐Chains, Higher Dispersibility, and Lower Equivalent Weight

Abstract: Interaction between the ionomer binder and catalyst nanoparticles in catalyst ink is well known to play an important role in the performance of proton exchange membrane fuel cells (PEMFCs) because it determines the final micro‐morphology of the catalyst layer. Herein, we investigated the 3M series of perfluorinated sulfonic acid (PFSA) ionomer binders, which have higher polymeric main‐chain mobilities, increased solubilities, shorter side‐chains, and lower equivalent weights than the Nafion 1100 series of iono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…This was attributed to the increased oxygen permeability, leading to enhanced mass transfer. Kim et al 399 proposed an SSC ionomer developed by 3 M (3 M ionomer) in an MEA to examine its effect on the performance. Optimization of the 3 M ionomer content showed that the optimal content was 25 wt %.…”
Section: Strategies Used To Improve the Performance Of Real-life Fuel...mentioning
confidence: 99%
“…This was attributed to the increased oxygen permeability, leading to enhanced mass transfer. Kim et al 399 proposed an SSC ionomer developed by 3 M (3 M ionomer) in an MEA to examine its effect on the performance. Optimization of the 3 M ionomer content showed that the optimal content was 25 wt %.…”
Section: Strategies Used To Improve the Performance Of Real-life Fuel...mentioning
confidence: 99%
“…[26] Figure 4 The molecular structure, the ionomer morphology in catalyst ink dispersions, and field emission scanning electron microscope (FESEM) surface images of the catalyst layer in the MEA: (a) Nafion 1100; (b) 3M 725 ionomers. [27] Reprinted with permission from Ref. [27].…”
Section: Ionomers Ionomer Typementioning
confidence: 99%
“…It has been commonly accepted that short side-chain ionomers are preferable to be the binders. [27][28][29][30][31][32][33] It has been greatly agreed that the proton conductivity can be improved with the increase of relative humidity. [34] Since the SSC ionomers usually have lower equivalent weight (EW) and better water absorption capability, their proton conductivities are higher than those of LSC ionomers, especially under low humidity conditions, resulting in a substantial performance improvement.…”
Section: Ionomers Ionomer Typementioning
confidence: 99%
See 2 more Smart Citations